2022
DOI: 10.1302/2046-3758.118.bjr-2021-0188.r1
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA H19 alleviates inflammation in osteoarthritis through interactions between TP53, IL-38, and IL-36 receptor

Abstract: Aims Osteoarthritis (OA) is a common degenerative joint disease characterized by chronic inflammatory articular cartilage degradation. Long noncoding RNAs (lncRNAs) have been previously indicated to play an important role in inflammation-related diseases. Herein, the current study set out to explore the involvement of lncRNA H19 in OA. Methods Firstly, OA mouse models and interleukin (IL)-1β-induced mouse chondrocytes were established. Expression patterns of IL-38 were determined in the synovial fluid and cart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 63 publications
1
18
0
1
Order By: Relevance
“…Excessive pro-inflammatory factors will trigger the upregulation of catabolic enzymes and downregulation of anabolic enzymes in chondrocytes, and ultimately contribute to the degradation of ECM, the deterioration of cartilage, and the occurrence of OA. [58][59][60] Our in vitro experiments confirmed that DHCA maintains the metabolic balance of chondrocytes by inhibiting inflammatory response. In addition, DMM method was a commonly used surgical strategy for establishing the OA cartilage.…”
Section: Discussionsupporting
confidence: 69%
“…Excessive pro-inflammatory factors will trigger the upregulation of catabolic enzymes and downregulation of anabolic enzymes in chondrocytes, and ultimately contribute to the degradation of ECM, the deterioration of cartilage, and the occurrence of OA. [58][59][60] Our in vitro experiments confirmed that DHCA maintains the metabolic balance of chondrocytes by inhibiting inflammatory response. In addition, DMM method was a commonly used surgical strategy for establishing the OA cartilage.…”
Section: Discussionsupporting
confidence: 69%
“…The long intergenic non-coding RNA, a regulator of reprogramming (linc-ROR), promotes mesenchymal stem cells’ chondrogenesis and cartilage formation via regulating Sox9 expression [ 42 ]. The upregulation of lncRNA H19 attenuates inflammation and ameliorates cartilage damage and chondrocyte apoptosis in OA by upregulating tumor protein p53 (TP53), IL-38, and by activating IL-36R [ 43 ]. A recent study also demonstrates that Sox9 keeps growth plates and articular cartilage healthy by inhibiting chondrocyte dedifferentiation/osteoblastic redifferentiation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutant TP53 can promote the development of inflammation by inhibiting secretory interleukin (IL)-1 receptor antagonists. 46 In addition, early TP53 mutation could promote NF-kB activation in the intestinal organs of mice, inducing severe chronic inflammation and continuous tissue damage in mice, thereby enhancing the predisposition to inflammationrelated colon cancer. 47 TP53 can reportedly reduce the production of inflammatory factors by regulating gene expression in inflammation-related signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have found that TP53 is closely related to non‐neoplastic diseases, such as inflammation and blood glucose regulation, in addition to cancer. Mutant TP53 can promote the development of inflammation by inhibiting secretory interleukin (IL)‐1 receptor antagonists 46 . In addition, early TP53 mutation could promote NF‐kB activation in the intestinal organs of mice, inducing severe chronic inflammation and continuous tissue damage in mice, thereby enhancing the predisposition to inflammation‐related colon cancer 47 .…”
Section: Discussionmentioning
confidence: 99%